2013
DOI: 10.1128/jcm.02360-12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Simple Blood Culture Amplification and Antigen Detection Method for Diagnosis of Salmonella enterica Serovar Typhi Bacteremia

Abstract: In most areas where typhoid is endemic, laboratory diagnosis is not possible due to the lack of appropriate facilities. We investigated whether the combination of blood culture amplification of Salmonella enterica serovar Typhi with an S. Typhi antigen rapid diagnostic test (RDT) could be an accurate and inexpensive tool for the accelerated diagnosis of patients with acute typhoid in Laos. For a panel of 23 Gram-negative reference pathogens, the Standard Diagnostics (catalog no. 15FK20; Kyonggi-do, South Korea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…9 A prospective study of the use of the rapid diagnostic test (RDT) (using OneStep Salmonella Typhi Ag Rapid Detection Kit; Standard Diagnostics, Kyonggi-do, South Korea) in Mahosot Hospital between September 2010 and December 2011 found S. Typhi in 30 (0.99%) of 3,028 blood cultures. 10 Subsequently, it was shown that gyrA mutations could be detected in RDTderived DNA to predict fluoroquinolone resistance in S. Typhi. 11 In a parallel article, we used data from sentinel surveillance from Mahosot Hospital over a 2-year period combined with a healthcare utilization survey in the hospital's main catchment area of Vientiane to develop an estimate of enteric fever incidence in the community.…”
Section: Introductionmentioning
confidence: 99%
“…9 A prospective study of the use of the rapid diagnostic test (RDT) (using OneStep Salmonella Typhi Ag Rapid Detection Kit; Standard Diagnostics, Kyonggi-do, South Korea) in Mahosot Hospital between September 2010 and December 2011 found S. Typhi in 30 (0.99%) of 3,028 blood cultures. 10 Subsequently, it was shown that gyrA mutations could be detected in RDTderived DNA to predict fluoroquinolone resistance in S. Typhi. 11 In a parallel article, we used data from sentinel surveillance from Mahosot Hospital over a 2-year period combined with a healthcare utilization survey in the hospital's main catchment area of Vientiane to develop an estimate of enteric fever incidence in the community.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 Typhoid diagnosis in the tropics could be enhanced by making the identification of S. typhi in blood cultures simpler, less expensive, and faster. 10 …”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated the utility of an antigen-detecting S . Typhi rapid diagnostic test (RDT) performed with blood culture fluid containing Gram-negative rods (GNRs) in typhoid diagnosis ( 9 ). As DNA extracts from RDTs and dried blood spots have been used for molecular surveillance of malaria and HIV drug resistance ( 10 12 ), we hypothesized that mutations in the gyrA gene could be detected from S .…”
Section: Textmentioning
confidence: 99%